2015
DOI: 10.1002/hbm.23088
|View full text |Cite
|
Sign up to set email alerts
|

Phasic and sustained brain responses in the amygdala and the bed nucleus of the stria terminalis during threat anticipation

Abstract: Several lines of evidence suggest that the amygdala and the bed nucleus of the stria terminalis (BNST) are differentially involved in phasic and sustained fear. Even though, results from neuroimaging studies support this distinction, a specific effect of a temporal dissociation with phasic responses to onset versus sustained responses during prolonged states of threat anticipation has not been shown yet. To explore this issue, we investigated brain activation during anticipation of threat in 38 healthy partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
98
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(108 citation statements)
references
References 70 publications
8
98
0
2
Order By: Relevance
“…Initial functional magnetic resonance imaging (fMRI) investigations of BNST function in humans have provided preliminary evidence that: the BNST is activated during anticipation of threat or reward loss (Alvarez et al, 2011; Grupe et al, 2013; Herrmann et al, 2016; Klumpers et al, 2015; Mcmenamin et al, 2014; Mobbs et al, 2010; Schlund et al, 2013); BNST activation is correlated with anxiety (Choi et al, 2012; Somerville et al, 2013, 2010) and childhood physical abuse (Banihashemi et al, 2013); and BNST activation is heightened in individuals with anxiety disorders (MĂŒnsterkötter et al, 2015; Straube et al, 2007; Yassa et al, 2012). Two recent papers provide thorough reviews of BNST fMRI findings in humans (Avery et al, 2016; Shackman and Fox, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial functional magnetic resonance imaging (fMRI) investigations of BNST function in humans have provided preliminary evidence that: the BNST is activated during anticipation of threat or reward loss (Alvarez et al, 2011; Grupe et al, 2013; Herrmann et al, 2016; Klumpers et al, 2015; Mcmenamin et al, 2014; Mobbs et al, 2010; Schlund et al, 2013); BNST activation is correlated with anxiety (Choi et al, 2012; Somerville et al, 2013, 2010) and childhood physical abuse (Banihashemi et al, 2013); and BNST activation is heightened in individuals with anxiety disorders (MĂŒnsterkötter et al, 2015; Straube et al, 2007; Yassa et al, 2012). Two recent papers provide thorough reviews of BNST fMRI findings in humans (Avery et al, 2016; Shackman and Fox, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent meta-analysis (Avery et al, 2016) demonstrated that the lack of an anatomical delineation of the human BNST has made it challenging to determine whether regions that show activation in fMRI studies truly encompass the BNST. Several studies report using a BNST region of interest defined on a 3 Tesla (3T) structural MRI (Alvarez et al, 2011; Banihashemi et al, 2013; Herrmann et al, 2016; Mcmenamin et al, 2014; Motzkin et al, 2015). While the use of BNST masks has been an important step forward, the gray matter/white matter/cerebrospinal fluid contrast afforded by standard 3T structural MRIs is typically insufficient to identify the anterior and posterior boundaries of the BNST.…”
Section: Introductionmentioning
confidence: 99%
“…Models of threat imminence processing (Fanselow and Lester, 1988) highlight the role of amygdalae in responding to upcoming threat (“post-encounter threat”; Mobbs et al, 2009) and to cues that signal potential or more distal threat (Herrmann et al, 2016), both relevant to speech anticipation. In healthy individuals, amygdala activation generally occurs rapidly in response to threat followed by fast deactivation (Breiter et al, 1996; Fischer et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The expected BOLD signal change for each condition was modelled with a canonical hemodynamic response function (HRF). For the anticipatory period, we calculated two different general linear models (GLM) (also see Herrmann et al, 2016). In the first GLM, the HRF was modelled over the whole phobia-specific and neutral anticipatory periods (sustained response).…”
Section: Methodsmentioning
confidence: 99%
“…The amygdala ROI was extracted from the anatomy toolbox (Eickhoff et al, 2005) and consisted of amygdala maximum probability maps as recommended by Eickhoff et al (2006) (also see Herrmann et al, 2016). ROIs for ACC, insula, PFC (dorsolateral superior frontal gyrus, medial superior frontal gyrus, middle frontal gyrus), OFC (orbital superior frontal gyrus, orbital middle frontal gyrus, orbital inferior frontal gyrus), thalamus and visual cortex (cuneus, fusiform gyrus) were defined on the basis of the Automated Anatomical Labeling (AAL) atlas included in the Wake Forest University (WFU) PickAtlas software (Maldjian et al, 2004, Maldjian et al, 2003, Tzourio-Mazoyer et al, 2002).…”
Section: Methodsmentioning
confidence: 99%